2017
DOI: 10.3892/ol.2017.7688
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of sodium-potassium ATPase regulator, FXYD3, in human hepatocellular carcinoma

Abstract: The clinical significance of the sodium-potassium ATPase regulator FXYD domain-containing ion transport regulator 3 (FXYD3) has been demonstrated in a number of types of cancer. However, the role of this protein in human hepatocellular carcinoma (HCC) remains to be elucidated. In the present study, 217 HCC tissue samples were analyzed to evaluate the expression and prognostic significance of FXYD3 in HCC. Reverse transcription-quantitative polymerase chain reaction was used to analyze the mRNA expression of FX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…It has been reported that FXYD3 is closely connected with the progression of various tumors [9,20,21]. However, the role of FXYD3 in CC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that FXYD3 is closely connected with the progression of various tumors [9,20,21]. However, the role of FXYD3 in CC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…FXYD domain containing ion transport regulator 3 (FXYD3), also named as mammary tumor 8, is a part of FXYD protein family and mainly distributed in cell membrane and cytoplasm [9]. It has been reported that FXYD3 functions as a regulator of sodium-potassium ATPase [10].…”
Section: Introductionmentioning
confidence: 99%
“…The family protein is a regulator of Na, K-ATPase, which plays an important role in the formation and maintenance of sodium and potassium ion transmembrane concentration gradients [ 17 ]. Meanwhile, members of the FXYD protein family such as FXYD3 and FXYD5 play an important role in the pathogenesis of numerous malignant tumors and are used as indicators for the biological characteristics and prognostic factors of certain tumors [ 18 , 19 , 20 , 21 ]. FXYD6 cDNA was first cloned in a rat hippocampus library by Yamaguchi [ 22 ], who named the encoded protein phosphohippolin, and FXYD6 protein was expressed highly in neurons and associated with neuronal cell development and synaptic signal transduction in a later research [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the clinical significance of the sodium-potassium ATPase regulator FXYD domain-containing transport regulator 3 (FXYD3) has been proved to have potential regulatory effects in a variety of cancers. In hepatocellular carcinoma, it can be used as an independent prognostic factor [29]. Studies have shown that FXYD3 is a multidrug resistance gene and plays an essential role in the multidrug resistance mechanism of hepatocellular carcinoma [30].…”
Section: Discussionmentioning
confidence: 99%